Sustainable implementation of the carbon-labeling policy with customer participation and government supervision. (April 2023) - Jiang, Ke; Zhang, Leilei; Zhang, Xiaojuan; Wang, Yusheng
Abstract: China is vigorously pursuing carbon neutrality targets to combat global warming. As a powerful tool for encouraging individuals to adjust their consumption patterns and fostering the advancement of green consumption, the overall planning of carbon-labeling policy is accelerating accordingly. To better comprehend and strengthen the sustainable implementation of carbon-labeling policy, this study constructs a tripartite mainstay game to explore the interactive behavior of carbon-labeled enterprises and customers, with the substantial involvement of governmental regulators. First, the evolutionary stability strategy (ESS) is determined by solving replicated dynamic equations and stability analysis of equilibrium points. Then, the practicability and rationality of the evolutionary game model are assessed ESSs corresponding to various scenarios in the carbon-labeling scheme. Finally, the first Chinese television manufacturer to acquire carbon-labeled certification, TCL Group, is utilized as evidence to validate the theoretical findings and support the subsequent arguments: There are eight equilibrium points and three potential ESSs in the game model, and the selection of each ESS is primarily determined by the trade-off between costs and revenues for each stakeholder; the level of carbon-labeled enterprises' green R&D effort has a beneficial effect on the implementation of carbon-labeling policy, while customers' identification of carbon-labeled products will potentially affect operational orientation; and governments' stringent oversight is a vital assurance that both the carbon-labeled enterprises and customers adhere to green initiatives. The results thus not only elaborate on the efficient approach and insights for the sustainable implementation of carbon-labeling policy with the participation of multiple stakeholders, but also offer suggestions for enhancing incentives to improve regulatory regimes and market outcomes. Highlights: Proposing a tripartite evolutional game in the carbon-labeled scheme. Performance of the strategy appears in a dynamic process of constant interaction. Government supervision is crucial for enterprises and customers to become green. Using numerical example to validate the theoretical outcomes.